The Welfare Cost of Market Power. Accounting for Intermediate Good Firms - Geir H. Bjertnæs (Statistics Norway, Research Department, 2007)
The market power of firms in intermediate good markets is found to generate a substantial welfare cost. Markup pricing of intermediate good firms contributes to increase the wedge between the marginal product of labor and the wage rate received by workers, as intermediate good firms add additional markups to the unit cost of a consumer good. This creates an additional wedge in the labor market, and is costly due to the existing substantial tax wedge in the labor market. The welfare cost of distortions in the supply of labor created by market power of firms is found to be more than 40 times larger than the welfare cost of distortions in the allocation of consumer goods created by differences in market power of firms. This welfare cost is substantial compared to previous estimates.
Keywords: D60; H20; 330; Monopoly; Taxation; Welfare costs